The Integration of Indigenous Knowledge for Disaster Risk Reduction Practices through Scientific Knowledge: Cases from Mentawai Islands, Indonesia - Zulfadrim Zulfadrim; Yusuke Toyoda; Hidehiko Kanegae (International Journal of Disaster Management, 2019)
This study explores the importance of indigenous knowledge for everyday practices of disaster risk reduction and response. Many existing studies have highlighted the need to integrate such knowledge with modern science. Based on ethnographic research in indigenous communities in the Mentawai Islands of Indonesia, this study explores the categorization of indigenous knowledge in the integration process. To that end, primary data were collected through in-depth interviews while secondary data were collected from relevant documents, including books, articles, websites and government and NGO reports. The findings indicate that indigenous knowledge is acquired through long observation and interaction with disasters. Although some of this knowledge is based on successes in other localities, some indigenous knowledge is completely local, homogenous and shared among community members. It was also established that indigenous knowledge can be meaningfully organized into a number of categories, and that indigenous knowledge of a technical nature is more likely to be integrated with scientific knowledge. The research was exploratory and approached indigenous knowledge issues from the point of view of indigenous communities themselves. This approach should be replicated and expanded in other indigenous communities.